Kajian tentang Timotius: Kepemimpinan dan Spiritualitas dalam Kondisi Fatherless - Loudy Benedictus Pranatha; Mariani Harmadi (Sekolah Tinggi Agama Kristen Terpadu Pesat, 2023)
This article explores the relationship between leadership and spirituality in the context of individuals experiencing the condition of "fatherlessness." The phenomenon of fatherlessness, where individuals grow up without a father figure in their lives, can have significant impacts on one's leadership development and spiritual aspects. Through a literature analysis of Timothy, a figure in the New Testament, this paper analyzes how an individual can cultivate leadership qualities and spirituality in the context of fatherlessness. The integration of these spiritual values provides a strong foundation for the development of authentic and meaningful leadership. This study offers new insights into how individuals facing fatherlessness challenges can overcome them through the development of spirituality-based leadership. Abstrak Artikel ini membahas tentang hubungan antara kepemimpinan dan spiritualitas dalam konteks individu yang mengalami kondisi fatherless. Fenomena fatherless, di mana individu tumbuh tanpa figur ayah dalam kehidupannya, dapat memiliki dampak signifikan terhadap perkembangan kepemimpinan dan aspek spiritualitas seseorang. Melalui kajian literatur mengenai Timotius, tokoh dalam Perjanjian Baru, makalah ini menganalisis bagaimana seorang individu dapat mengembangkan kualitas kepemimpinan dan spiritualitasnya dalam kondisi fatherless. Integrasi nilai-nilai spiritual ini memberikan landasan yang kuat bagi pengembangan kepemimpinan yang autentik dan bermakna. Studi ini memberikan wawasan baru tentang bagaimana individu dalam kondisi fatherless dapat mengatasi tantangan tersebut melalui pengembangan kepemimpinan yang berbasis spiritualitas.